Gender features of regulatory relationships of homocysteine, pituitary and thyroid hormones in children from areas affected by the accident at the Chornobyl nuclear power plant (Environment & Health, 2024)
The purpose of the work was to determine gender characteristics in the formation of regulatory connections between homocysteine (Hcy), pituitary and thyroid hormones in children from regions of Ukraine affected by the accident at the Chornobyl nuclear power plant.Materials and methods: analytical, genetic, laboratory, mathematical and statistical.Results: 379 adolescents (187 boys and 192 girls) from the Ivankyvskyi and Polyskyi districts of the Kyiv region were examined. The amount of Hcy, pituitary thyroid-stimulating hormone (TSH), free triiodothyronine (T3), and free thyroxine (T4) was determined in the blood of children. A study was conducted on the state of the genetic system of the folate cycle (FC). In the group of boys from the Polyskyi district, the content of Hcy, TSH, T3 in the blood was significantly more than in the group of girls. After forest fires in the Chornobyl Exclusion Zone (ChEZ), the blood levels of Hcy, T3, and T4 in girls from the Ivankyvskyi district were significantly more than in girls from the Polyskyi district. When Hcy concentrations in the blood did not exceed 10.0 µmol/l, in subgroups of children examined, a direct relationship was recorded between the values of Hcy and T4, indicating a certain physiological parity between the FC and the pituitary-thyroid axis. At Hcy concentrations exceeding 10.0 µmol/l in subgroups of children, the stimulating effect of TSH on the process of T3 formation was revealed by reducing the T4 content. The process of stimulating the activity of FC enzymes with the help of T3, represented by the Hcy-T3 and Hcy-T3/T4 feedbacks, is most pronounced in the group of girls compared to the group of boys. This may be the reason that they have less Hcy in their blood.Conclusions: An increase in the concentration of Hcy in the blood and an increase in the formation of T3 under the influence of TSH in the body of the examined children is associated with a genetic factor (allele T MTHFR:677 in the genome). The pronounced external radiation impact associated with forest fires in the ChEZ contributed to a significant increase in the content of Hcy in the blood and an increase in the influence of TSH on the processes of thyroid metabolism in children from adjacent settlements. T3 has a stimulating effect on FC enzymes, which leads to increased Hcy methylation and increased formation of internal methionine.
Keywords: folate cycle; homocysteine; pituitary and thyroid hormones; children; radioactively contaminated areas